Penilaian Risiko Kualitatif Masuk dan Tersebarnya Rabies pada Anjing ke Kota Sorong Provinsi Papua Barat - Muchammad Taufik Kurniawan; Heru Susetya; Bambang Sumiarto (Jurnal Sain Veteriner, 2018)
The rabies outbreaks of Indonesia in these two decades tends to spread faster to other islands/regions. Trade trafficking and people's habits of carrying dogs between islands are contributing factor that triggers rabies cases in Provinces previously free of rabies. This study aims to qualitative risk assessment entry and spread of rabies in dogs into Sorong City of West Papua Province. Methods of collecting primary data obtained from expert opinions, questionnaires, interviews, and direct observation in the field. Secondary data is taken through search of scientific publications, surveillance results, unpublished data in the form of reports, and documents from authorized agencies. The results of study showed that release assessment was high, the incidence of rabies in dogs was 52%, and 180 cases of rabies in humans (lyssa) in Sulawesi, Maluku and North Maluku. The exposure assessment was high based on the presence of rabies transmite animal (RTA) traffic from endemic areas, 58% dogs, 38% cats, and 4% apes from Java 68% (Surabaya 50%, Jakarta 18%), Sulawesi 10% (Manado and Bitung), Maluku 14% (Ambon) and North Maluku 8% (Ternate). The consequence assessment is high because there is a single impact that is categorized as nationally significant. The estimated risk of getting into rabies is high. The potential pathways used in RTA traffic to Sorong City is by sea at 89.3% and air at 10.7%. The results of the study concluded that the qualitative risk assessment of entry and spread of rabies in dogs to the Sorong City of West Papua Province was high. All risk assessments have low uncertainty.